Facing an unexpected challenge: How Special Education Teacher Happy? - Dwi Talita, Eliyan; Eka Izzaty, Rita; Rohmah Nurhayati, Siti (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Happiness has a different meaning for special education teachers due to facing the challages such as aggressive behavior, pressure from special children, and blocking their emotion. Aim to this study to deeply understand how special education teacher happiness. A qualitative phenomenological approach was used in this study by collecting data base on in-depth interview dan observations. Participants that involved in this study was special education teacher had worked for more than two years. Data analysis were carried out by condentation data, coding, and syntesis. The results of this study showed that the happiness of special education teachers was divided into main themes, positive relationship with others, positive emotions, optimism, finding meaning, and involvement. Happiness of special education teachers was influenced by spirituality, work experience, and income. Meaning of happines from special education teachers was defided by how their can control reaction from facing uncertainty challenges and look from different ways.